A study of terpenes and undesirable flavour compounds in grapes and wine and the application of 13C nuclear magnetic resonance spectroscopy in wine analysis - Rapp, Adolf (Stellenbosch : Stellenbosch University, 2012)
On t.p. 13 is superscript.